An analysis of the impact of refugees on security: the case of Zimbabwe, 2012-2017 - Marongere, Herbson (Midlands State University, 2019)
The increase in the number of refugees in Zimbabwe has seen many even the national assembly claiming that this is why there are cases of crimes, human trafficking, budget deficit and other socio-economic and political threats. The research was influenced by a high rise in influx of refugees into Zimbabwe who are migrating from war torn region the African Great Lakes Region (AGLR) in particular the Democratic Republic of Congo (DRC). Refugees are viewed as a security threat in different facets; politically, socially, economically and militarily. The research sought to unravel the concept of refugees, analyse the effects on the influx of refugees on host countries, proffer scholarly and policy recommendations on sustainable measures to deal with refugee increase. The research was guided by the two theories; Neoclassical Theory of Migration (NTM) and New Economics of Labour Migration (NELM). The research was a case study approach, adopted descriptive research design and employed both qualitative and quantitative research methods. Study population was 590 and sample of 120 participants. Sampling techniques used were purposive and random sampling. Sources of data include a secondary source that is published scholarly material, reports, journals and newspapers. Primary data was gathered through questionnaires and interviews. The major findings from the study are that refugees were perceived as posing a range of threats to Zimbabwe, which were criminal, economic, political, terrorist and social in nature. For instance, in social terms, the biggest threats were perceived as affecting the health, followed by culture, ethnic identity and religion of the indigenous population. Moreso the country has poor capacities to deal with any security related problems emanating from refugee influx, including screening of refugees for security threat, knowing refugees’ real identities, tracing refugees’ identities back to their home countries for criminal and illegal activities, regulation of border entries to prevent illegal and criminal immigrants, and knowing the whereabouts of each refugee within the borders of Zimbabwe. As a way of potentially dealing with the security threats posed by the influx of refugees it is recommended that proper refugee screening at borders, reducing levels of border “jumping”, removing the refugee camp (i.e. Tongogara Refugee Camp) from the Border Town, providing police company to refugees on their way from the border to the refugee camp, providing a secure refugee camp, and imposing national refugee quotas per annum. The findings from this research will be used by policy makers in understanding security threat posed by the influx of refugees into Zimbabwe and how best to deal with the refugees situation without causing a diplomatic spat within the international arena.